2022
DOI: 10.1111/cge.14190
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and neurobehavioral characterization of two frequent forms of neurodevelopmental disorders: the DYRK1A and the Wiedemann–Steiner syndromes

Abstract: DYRK1A and Wiedemann–Steiner syndromes (WSS) are two genetic conditions associated with neurodevelopmental disorders (NDDs). Although their clinical phenotype has been described, their behavioral phenotype has not systematically been studied using standardized assessment tools. To characterize the latter, we conducted a retrospective study, collecting data on developmental history, autism spectrum disorder (ASD), adaptive functioning, behavioral assessments, and sensory processing of individuals with these syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The rate of anxiety by history and by current clinical symptoms are elevated in our sample in contrast to prior observational studies or case reports (Chan et al, 2019), which reported about 10% of their cohort of persons with WSS had a history of anxiety. However, our study findings, which showed approximately 33% of participants met clinical threshold on the SCARED/SCAARED, were similar to Durand et al (2022), which reported 38% of their sample with WSS yielded a SCARED total score indicative of clinical anxiety. Discrepancies in findings may be due to methodological differences as published literature on those with WSS largely relies on retrospective chart review or natural history rather than standardized screening tools.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of anxiety by history and by current clinical symptoms are elevated in our sample in contrast to prior observational studies or case reports (Chan et al, 2019), which reported about 10% of their cohort of persons with WSS had a history of anxiety. However, our study findings, which showed approximately 33% of participants met clinical threshold on the SCARED/SCAARED, were similar to Durand et al (2022), which reported 38% of their sample with WSS yielded a SCARED total score indicative of clinical anxiety. Discrepancies in findings may be due to methodological differences as published literature on those with WSS largely relies on retrospective chart review or natural history rather than standardized screening tools.…”
Section: Discussionsupporting
confidence: 91%
“…The clinical exploration of behavioural phenotypes revealed the importance of anxiety symptomatology and signs of ADHD in patients with WSS, also reported in GenIDA. This study, describing the behavioural and neurocognitive profiles of individuals with WSS and DYRK1A syndrome, highlighted some important specificities to be addressed in patients' management (Durand et al 2022 ).…”
Section: Case Studiesmentioning
confidence: 91%
“…Most participants met criteria for both ASD and ID, indicating that social communication challenges in DYRK1A syndrome are frequently above and beyond those expected based on developmental level. Previous reports of lower rates of ASD diagnoses in this population may have been confounded by variable access to a multi‐method ASD diagnostic assessment (e.g., delays due to long waitlists, distance from assessment providers) combined with features of ASD that may be overshadowed by cognitive deficits, medical complexity, and sensory impairments in individuals with syndromic ID (Durand et al, 2022; Thurm et al, 2019). These results highlight the importance of standardized deep phenotyping that utilizes multiple measurement types and informants in characterization of rare ASD‐associated genetic disorders.…”
Section: Discussionmentioning
confidence: 92%
“…It is unknown whether these participants were previously evaluated for ASD and did not meet the criteria, whether they have not yet been able to access an ASD evaluation, or whether ASD is not currently of clinical concern for these participants. Durand et al (2022) found that 57% of individuals with DYRK1A syndrome met criteria for ASD on the Autism Diagnostic Interview‐Revised, which may or may not fully correspond with the expert clinical diagnosis of ASD using a multi‐method assessment approach (Thurm et al, 2019). Finally, both phenotyping batteries and ASD diagnostic thresholds may vary widely across studies, which limits the ability to draw conclusions about true ASD prevalence when individuals with DYRK1A syndrome are combined or compared (Myers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%